A Unified Strategy Toward 5‐, 6‐, and 7‐Membered Nitrogen Heterocycles Through Free Radical then Metal‐Mediated Functionalization of Ene‐carbamates. Issue 18 (6th September 2017) - Beniazza, Redouane; Poittevin, Clément; Lusseau, Jonathan; Massip, Stéphane; Robert, Frédéric; Landais, Yannick
Abstract: Free‐radical carbo‐alkenylation of N ‐aryl‐, N ‐benzyl‐, and N ‐phenethyl‐ene‐carbamates with a disulfone provides vinyl sulfones which may then be functionalized and engaged in Heck‐type coupling to furnish highly substituted 5‐, 6‐ and 7‐membered nitrogen heterocycles. Grignard‐mediated cyclization starting from the same substrates further allowed a nucleophilic cascade process, affording a straightforward access to hydrocarbazoles, which may be regarded as potent intermediates for the synthesis of alkaloids of the Aspidosperma family. Abstract :